Fixed-Bed Column for the Removal of Cd(II) from Aqueous by Hydroxyapatite from Red Snapper (Lutjanus campechanus) Fish Bone - Widia Purwaningrum; Fahma Riyanti; Muhammad Said; Poedji Loekitowati Hariani; Aria Septi Handayani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
The Synthesis of hydroxyapatite from Red Snapper (Lutjanus campechanus) fish bone carried out. Hydroxyapatite is utilized for Cd(II) sorption from solution using a fixed-bed column. Hydroxyapatite was characterized using X-ray Diffraction, Fourier Transform Infra-Red, Scanning Electron Microscope-Electron Dispersive, and Thermogravimetric. In fixed-bed column, the influence of bed height (5, 10, 15 cm) and flow rate (6, 8 and 10 mL/min) were studied. The highest adsorption capacity is obtained at a bed height of 15 cm, and a flow rate of 6 mL/min with adsorption capacity is 47.027 mg/g. The predicted by Bed Depth Service Time (BDST) model obtained that value of R2 in the range 0.9964-0.9997. The adsorption capacity per unit volume ( is in the range 141.12-222.89 mg/L while is in the range 0.0136-0.022 L/mg h. This indicates that BDST can be used to explain the performance of Cd(II) sorption onto hydroxyapatite by fix-bed column.